Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 446 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Crotalus atrox Baird & Girard, 1853", "Country is Mexico", "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 446 records from 20 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0007312-160118175350007/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences